Quantifying the economic impact and management strategies for foot rot (Phytophthora capsici L.) disease on black pepper cultivation in West Coast India: Farm-level insights - Bhat, S; Arunachalam, V; Paramesha, V; Gaonkar, N (Plant Science Today, 2025)
Foot rot disease, caused by the soil-borne fungus Phytophthora capsici, poses a severe threat to black pepper cultivation, particularly in the Western Ghats region of India. The current study aims to comprehensively assess the economic impact of foot rot disease on black pepper cultivation in Goa and coastal Karnataka, focusing on farm-level losses, considering both present year yield losses and replacement costs given the perennial nature of the vine. The findings reveal an average vine mortality rate of 9.64% due to foot rot, leading to an economic loss of USD 902.04/ha, equivalent to 56% of annual net returns. Using a dummy variable regression model, the effectiveness of various management practices employed by farmers in mitigating foot rot disease was assessed. The study shows that adopting management practices, such as avoiding water stagnation and ensuring good drainage, reduced losses caused by foot rot by 24% (USD 439/ha), while the use of fungicides led to a 20% reduction (USD 364/ha and in the absence of foot rot management strategies, the loss amounted to USD 1838/ha. In conclusion, educating farmers and promoting the adoption of integrated disease management practices can reduce foot rot losses, thereby enabling sustainable production and improved income from black pepper.